Assessment of the application for renewal of authorisation of AveMix® XG 10 (endo‐1, 4‐beta‐xylanase and endo‐1, 3(4)‐beta‐glucanase) for chickens for fattening. (22nd April 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of AveMix ® XG 10 (endo‐1, 4‐beta‐xylanase and endo‐1, 3(4)‐beta‐glucanase) for chickens for fattening. The applicant has provided evidence that the additive currently in the market complies with the existing conditions of authorisation. There is no new evidence that would lead the FEEDAP Panel to reconsider its previous conclusions. Thus, the Panel concludes that the additive remains safe for the target species, consumer and the environment under the authorised conditions of use. Regarding user safety, the additive is not considered to be a dermal or eye irritant but it is a dermal and respiratory sensitiser. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.